EVALUASI PELAKSANAAN SISTEM INFORMASI RUJUKAN KESEHATAN IBU DAN BAYI BARU LAHIR (SIKIBBLA) DI KABUPATEN BANDUNG TAHUN 2024 - Pamungkas, Gugum; Febriani, Weny; Tusrini, Weny; Surtimanah, Tuti (Jurnal Ilmu Kesehatan Immanuel, 2024)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) are still strategic issues. One of the programs to reduce MMR and IMR is to increase the effectiveness and efficiency of the referral system in the form of an information system by utilizing advances in information technology. SIKIBBLA is one of the innovations in Bandung Regency which is an information technology-based referral information system saving mothers and babies. However, in its implementation there was a decrease in the number of referrals through the SIKIBBLA call center and an increase in the number of infant deaths in Bandung Regency. This study aims to evaluate the implementation of SIKIBBLA in Bandung Regency in 2024 based on input, process and output components. The research was conducted using a qualitative method through in-depth interviews with 7 informants. The results of the research on the input component show that a special budget is not yet available. Human resources are sufficient, but further training on referral procedures is needed. Facilities and infrastructure are adequate, with information systems used via telephone, WhatsApp and Telegram. However, there is no regulation regarding SIKIBBLA in Bandung Regency. In the process component, all levels of health services have SOPs that facilitate the implementation of referral procedures, thus ensuring that every step taken is in accordance with the provisions. The Health Office acts as a communication link between the Puskesmas and the hospital. But there are still obstacles that can affect the smoothness of the referral process. In the output component, a recap report is conducted every month and submitted to the leadership as an evaluation of the problems found. Puskesmas and hospitals have measured satisfaction levels, but the Health Office has not done so. Conclusion: The Health Office needs to increase the training budget for health workers at Puskesmas, Hospitals and call center officers in handling referrals and conduct periodic monitoring and evaluation of health facilities, especially hospitals related to the implementation and effectiveness of referral procedures.